Speech act of political figures in the discourse of educational development: an interpersonal pragmatic approach - Dina Mardiana; Fathur Rokhman; Rustono; Hari Bakti Mardikantoro (Cogent Arts & Humanities)
This study analyzes the speech acts of political figures in Commission X of the Indonesian House of Representatives (Komisi X DPR RI) within the context of educational development discourse. Drawing on interpersonal pragmatics, the study critically evaluates the pragmatic force of political speeches, focusing on politeness strategies as outlined by Leech and Brown & Levinson, alongside Grice’s cooperative principle. An analysis of 66 public utterances from 2019 to 2024 reveals that while the majority of speech acts (86.4%) adhere to politeness conventions, 13.6% involve violations. These utterances reflect political figures’ attempts to influence, persuade, and criticize government policies, often employing irony and hyperbole as rhetorical strategies. The findings emphasize the importance of maintaining politeness in political discourse, especially in shaping public opinion and influencing educational policy. The study suggests that political figures should serve as role models by adhering to conversational principles while representing the public’s aspirations. Furthermore, it highlights the need for a strategic framework to guide political figures in maintaining politeness, contributing to more cooperative and respectful parliamentary dialogue.